Ecology of Wild Hogs in Florida - William M. Giuliano; George W. Tanner (EDIS, 2005)
Florida's wild hogs (Figure 1) are often referred to as feral hogs or swine and are of three general types. These include free-ranging swine that come from domesticated stock, Eurasian wild boar, and hybrids of the two. Although technically, feral refers to free-ranging animals from domesticated stock, all wild hogs are typically referred to as feral in Florida and all are considered the same species, Sus scrofa. Wild hogs are in the family Suidae (true wild pigs), none of which are native to the Americas. Although not found in Florida, the only native pig-like mammal found in the United States is the collared peccary or javelina (Tayassu tajacu; Figure 2). These are not true pigs, in the family Tayassuidae, and about half the size of typical wild hogs. This document is WEC 191 and is one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: April 2005.